ANALISA KEBUTUHAN FASILITAS PENYEBERANGAN JALAN DI DEPAN KAMPUS FT. UNTIRTA KOTA CILEGON - Budiman, Arief; Suryani, Irma; Wijianto, Rio (FSTPT Indonesia, 2015)
This study discusses about the road crossing facilities in front of the campus FT. Untirta which is located in the Cilegon city and there are facilities such as zebra crossing street is not feasible. Therefore, it is necessary to analyze the needs of the road crossing facilities in front of the campus FT. Untirta which aims to find out a viable path crossing facilities and to find out the design of the road crossing facilities. Analyze the needs of the road crossing facilities using the guidance from the Departement of Public Works Directorate Bina Marga 1995 on Procedure for Planning Pedestrian Facilities in Urban Area using the formula PV2 where P is the pedestrian volume (person/hour) and V is the volume of vehicle flow (vehicle/hour) and for designing a road crossing facilities using google sketchup pro 8. The result of research that the volume of vehicular traffic and pedestrian volumes in the PV2 formula have a maximum of PV2 formula at 17.00 to 18.00 with P = 250 person/hour, V = 5639 Vehicle/hour, and then generate PV2 = 6518655805 or 6 x 109 and the result in the table adjusted to the determination of pedestrian crossing facilities according Bina Marga which generate a pelican crossing with a criteria P = 59 – 1100 person/hour, V = 700 vehicle/hour, and PV2 = >2 x 108. Projection result in a period of 5 years generating road crossing facilities that recommended are crossing the road bridge.